The Singer and the Voice. Vocal Physiology and Technique for Singers - Rose, Arnold (London The Scolar Press, 1978)
Why is the teaching of singing virtually at a standstill when so much new scientific knowledge is available? Arnold Rose's question is at the heart of this challenging book. His answer is that too few teachers know enough about what really happens when a voice is used, and that until they do their methods will be ineffective if not downright harmful. The Singer and the Voice uses fundamental research into acoustics and physiology, and combines these with nearly three decades of practical experience to devise exciting new techniques of voice production and control.
Huys
Keywords: Method; Singing